Kajian Sifat Kimia Inceptisol Pada Beberapa Kelas Lereng Di Nagari Aie Dingin Kecamatan Lembah Gumanti Kabupaten Solok - Andini, Liza; Prasetyo, Teguh Budi; Rasyidin, Azwar (Journal Arunasita, 2025)
A study on chemical properties of Inceptisols in four slope classes in scrubland areas was conducted in Nagari Aie Dingin, Lembeh Gumanti Sub-District, Solok Regency, from May 2022 to February 2023. This research was aimed to assess the chemical properties of Inceptisols in several slope classes in Nagari Aie Dingin, Lembah Gumanti Sub-District, Solok Regency. The study was carried out using a survey method. Samples were purposively taken from four slope classes (8-15%, 15-25%, 25-45%, >45%) and one comparison land (25-45%) at depths of 0-20 cm and 20-40 cm with three replications. The parameters analyzed were soil pH, organic C, total N, C/N ratio, available P, and CEC. The research results indicated that the soil pH ranged from 4.61 units to 5.62 units (acidic to slightly acidic). The organic carbon content of the soil ranged from 1.51% to 2.55% (low to moderate). The total nitrogen content ranged from 0.05% to 0.19% (very low to low). The C/N ratio ranged from 9.37 to 35.8 (low to very high). The P-available content ranged from 2.29 ppm to 43.6 ppm (very low to very high). Cation exchange capacity (CEC) had values from 14.28 me/100g to 43.62 me/100g (low to very high). The result showed that in the research area there was a decrease in the value of soil chemical properties along with increasing slope class.